LIS education and cultural heritage information management - Kouis, Dimitris; Kyriaki-Manessi, Daphne; Giannakopoulos, Georgios (Journal of Integrated Information Management, 2019)
Purpose - It has been more than two decades that LIS Education has been regarding information organizations (libraries, archives and museums) as an integrated field sharing a common basis of acquiring, handling and disseminating information independently of its source or substrate. LIS curriculum has treated resources at the basis of their descriptive, structural and administrative metadata; their semantic value; and the employment of technology as the means for creating a common platform for its organization, accessing and dissemination purposes. Design/methodology/approach - LIS curriculum has expanded in order to meet the informational needs of cultural heritage institutions, such as museums and cultural centers. Their requisites to create the fundamentals for their digital information management and digital presence in the web and their obligations to supply information and communicate with each other became also part of the curriculum. This introduced almost simultaneously the need to operate in common environment with archives and libraries that not only hold a significant amount of related information but also have common operational attributes. The latter has brought forward issues of interoperability, communication between metadata standards, the use of controlled vocabularies and semantic representation techniques. All of the above, have established the notion in LIS Education that libraries, archives and museums are a global network of information organizations. A series of cultural heritage projects, funded through the Horizon2020 call were focusing on employing new technologies for staging cultural heritage content. The need for metadata and semantics had acquired the expertise of information professionals. Herein, the case of the curriculum reform of the Department of Archives, Library and information Studies of the University of West Attica is presented and the specific interrelationship of the Horizon2020 Project “CrossCult” in which the aforementioned Department participated, is viewed as a parameter for shaping a cluster of courses within its curriculum.